African Chicken Genetic Gains (ACGG) - Baseline Data - Dessie, Tadelle; Sonaiya, Prof. Funso; Guangul, Solomon; Hamisi Goromela, Dr. Ezekiel; Bruno, Jasmine; Getachew, Fasil; Poole, Elizabeth; Komen, Hans; Jaramillo, Ms Maria; Hanotte, Olivier; Assefa, Getnet; Esatu, Wondmeneh; et al. (International Livestock Research Institute, 2016)
A program for accessing, testing, adapting, and catalyzing public-private partnerships for multiplying and making available well-adapted low-input chickens for productivity growth in sub-Saharan Africa.